4D printing of products based on soy protein isolate via microwave heating for flavor development. (November 2020) - Phuhongsung, Pattarapon; Zhang, Min; Bhandari, Bhesh
Graphical abstract: Highlights: The mixtures of SPI, k -carrageenan and vanilla flavor was established for 4D printing. The flavor of 3D printed products were affected by different powers from microwave at 50, 80 and 110 W for 5 min. Higher temperature potentially induced dominant flavor of the 3D printed products. Abstract: The aim of this study is to establish food 4D printing products with the property of automatic flavor change by the post-printing application of microwave as an external thermal stimulus. The combination of a formulation comprised of soybean protein isolate (SPI), k -carrageenan (CAR) and vanilla flavor (VNL) was used as printing material. The change in flavor profile was observed by the level of external heat stimulus as a 4D effect. The results of e-nose revealed a significant difference ( P  < 0.05) in sensors 2, 5, 6, 9, 10, 12 and 13 in the sample added with vanilla flavor meanwhile GC–MS detected 25 volatiles compounds. Notably, four new generated flavor compounds (1-Octen-3-ol, Maltol, Ethyl maltol and eugenal) were identified when added with vanilla flavor. Moreover, e-tongue results indicated the taste characteristics of the sample with vanilla flavor presenting more intense bitterness, astringency, umami, richness and saltiness. The rheological property and water distribution (LF-NMR) determined at different concentrations levels of carrageenan showed that SPI gel made with 3% (w/v) carrageenan was the most suitable for 3D printing among all three concentrations considered in this study. Overall, the results can conclude that the addition of carrageenan and post-printing microwave heating at an optimum level of microwave power enhanced the printability and flavor of SPI gel.